Perceptions and practices of tribal traditional healers of Barwani district in Madhya Pradesh: a mixed-method study - Kirthana V.; Shilpa Ravi; Vaibhavi Umesh Tailor; Shailendra Kumar B. Hegde; Mandar Randive (International Journal Of Community Medicine And Public Health, 2026)
Background: Tribal traditional healers are integral to tribal cultures and strongly influence community health behaviors and decisions. Achieving Universal Health Coverage (UHC) in tribal areas requires collaboration with these healers. Recognizing this, the WHO recommends strengthening traditional healing systems through capacity building and standardization of practices. This study aimed to describe ritualistic and non-ritualistic healing practices of tribal healers in selected states, determine the knowledge and attitude of TTHs on other systems of medicine. Methods: A cross-sectional mixed-methods design was used, involving 275 healers from Barwani district for quantitative analysis and five for qualitative exploration. Quantitative data were analyzed using the Kruskal-Wallis-H test and Poisson regression and thematic analysis of qualitative data was performed. Results: Findings reported that 211 (99.06%) of 213 Barela healers and 57 (91.93%) of 62 Bhil and Bhilala healers had very poor knowledge of other medical systems. Similarly, 207 (97.18%) Barela healers and 56 (90.32%) Bhil/Bhilala healers were not inclined toward adopting other health systems. Education reported a statistically significant association with knowledge levels. Qualitative analysis generated four key themes: understanding disease and the diseased, diagnostic approaches, treatment practices, and government support. The study recommends development of interventions, capacity-building sessions and behaviour change communication strategies that are culturally acceptable to tribal healers and thereby, developing strategies by fostering collaboration with them to achieve universal health coverage. Conclusions: In a nutshell, culturally acceptable strategies to integrate tribal healers into PHS are the way ahead to achieve UHC. While studies in different contexts reported TTHs playing significant roles in disease awareness, current study emphasized the masked factors in terms of low knowledge of healers and no inclination towards OHS. Without targeted interventions involving their cultural beliefs and practices, it is challenging not just achieving UHC but also ensuring primary healthcare. The current study strongly recommends a large-scale research to understand the avenues to integrate TTHs into PHS. It also emphasise developing collaborative care models by capacity building of healers and establishing effective referral linkages.